The Relationship between Working Demands and Work-family Conflict: The Role of Stress - Pinho, José Carlos; Santos, Gina; Menezes, Carlos; Fontes , Alexandra (Conferência - Investigação e Intervenção em Recursos Humanos, 2024)
We apply the Conservation of Resources theory to study how work demands impact work-family conflict through stress and the role of control over working time in this relationship. Balancing work and family life presents increasing challenges in modern societies, with demands at work and home leading to potential role conflict. Work-family conflict (WFC) can arise in three ways: time-based conflict, strain-based conflict, and behavior-based conflict. This conflict can occur bidirectionally, with work demands affecting family needs (work-to-family conflict) or family commitments interfering with work responsibilities (family-to-work conflict) From a methodological perspective, we adopted a quantitative study using an online questionnaire. The data was obtained from an online survey of professional accountants. The 4833 questionnaires valid for our research represent nearly 80% of our initial sample. We employed the PLS-SEM approach using Smart PLS 4.0 software to analyze the results. The results show that stress can cause an ongoing depletion of resources, causing individuals to lose emotional resilience, time, and energy. Overall, work demands can start a cycle of resource loss, where stress depletes resources. Therefore, quantitative and emotional work demands significantly impact WFC directly and indirectly through stress. In terms of contribution, we found that having control over working time does not significantly reduce the impact of stress on work-family conflict. Following the Conservation of Resources theory principles, we found that resource recovery requires more than just flexible scheduling; it necessitates substantial replenishment of resources, which control over working time might not provide.